Revival and Transition: Evolving Roles and Various Forms of Informative Graphics - Lin, Tingyi S. (InfoDesign, 2019)
Currently, informative graphics has attracted considerable attention for its efficient and effective methods of communication. The ways in which people receive information strongly influence their ability not only to comprehend the information but also to capitalize on the purported benefits of the information. Information-design approaches can facilitate the creation of many good-quality designs. By understanding both the history of information design and pertinent case studies, we can familiarize ourselves with information-design methods and applications. In this article, I discuss the evolution and various forms of informative graphics on the basis of historical, content-oriented, and phenomenological analyses. I investigate visual representations’ roles and identify the strengths and deficiencies of visual communication for information design. Historical evidence—such as Playfair’s graphic charts and his method, Winderlich’s clinical graphics, Nightingale’s statistical graphs, and Snow’s dot maps—show that appropriate visual formats can depict data and that these depictions can demonstrate effects over time. The graphical method can also aid in the measurement of small-time intervals between biological effects. Multiple variables enhance the exploratory power of graphics in relation to analysis and discovery. Narrative graphics associate the spatial dimension with time-series displays to depict space and time. Although many disciplines acknowledge “the importance of communication,” the general public in Taiwan has only recently begun to acknowledge the importance of informative graphics. We should reflect now and then on the evolution and various forms of informative graphics.